BLITZKRIEG TO DESERT STORM: THE EVOLUTION OF OPERATIONAL WARFARE/ROBERT M. CITINO - Nabbie, Cadene (Scientia Militaria - South African Journal of Military Studies, 2011)
Robert Michael Citino is an American history professor, scholar and author specialising in German military history. This extensive work on German military history and the credentials of the author make the book a credible source of information. The book seems biased in depicting the German military as the best but if one is acquainted with military history, it is a bias that could be justified. Citino states boldly in the introduction that the German invasion of France in May 1940 should be seen as a day that changed the world. The magnificent skill employed by the German military indeed represented a profound contrast to the disease of stalemates infecting militaries before the Second World War. The invasion did not change the world; instead, it brought about an increased awareness of the importance of the operational level of war, a dimension of warfare previously neglected. The German operational effectiveness represented an evolution rather than a revolution in operational thinking. Although revolutions may have specific dates attached to them, evolutions do not. The Germans were successful in adapting their operational thinking to new demands. This adaptation did not occur in May 1940. It was a process which included war simulations and various other developments. Although Citino’s statement that the “world changed in May 1940” and other such statements referring to a “revolution” may be flawed, the rest of the book certainly is not. The “evolutionary” concept is definitely captured throughout the book.